National audit of a system for rectal contact brachytherapy. (January 2017) - Humbert-Vidan, Laia; Sander, Thorsten; Eaton, David J.; Clark, Catharine H.
Highlights: Four Papillon 50 contact brachytherapy machines audited. All results within clinically acceptable accuracy. Optimisation of HVL jig design and film analysis methodology recommended. Abstract: Background and purpose: Contact brachytherapy is used for the treatment of early rectal cancer. An overview of the current status of quality assurance of the rectal contact brachytherapy systems in the UK, based on a national audit, was undertaken in order to assist users in optimising their own practices. Material and methods: Four UK centres using the Papillon 50 contact brachytherapy system were audited. Measurements included beam quality, output and radiation field size and uniformity. Test frequencies and tolerances were reviewed and compared to both existing recommendations and published reviews on other kV and electronic brachytherapy systems. External validation of dosimetric measurements was provided by the National Physical Laboratory. Results: The maximum host/audit discrepancy in beam quality determination was 6.5%; this resulted in absorbed dose variations of 0.2%. The host/audit agreement in absorbed dose determination was within 2.2%. The median of the radiation field uniformity measurements was 2.7% and the host/audit agreement in field size was within 1 mm. Test tolerances and frequencies were within the national recommendations for kV units. Conclusions: The dosimetric characterisation of the Papillon 50 was validated by the audit measurements for all participating centres, thus providing reassurance that the implementation had been performed within the standards stated in previously published audit work and recommendations for kV and electronic brachytherapy units. However, optimised and standardised quality assurance testing could be achieved by reducing some methodological differences observed.